2018
DOI: 10.1186/s12889-018-5371-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for the occurrence of multidrug-resistant tuberculosis among patients undergoing multidrug-resistant tuberculosis treatment in East Shoa, Ethiopia

Abstract: BackgroundMultidrug-resistant tuberculosis (MDR-TB) is resistant to the two main first-line anti-tuberculosis drugs: rifampicin and isoniazid. It is a major threat to public health worldwide. The objective of this study was to assess the potential risk factors for multidrug-resistant tuberculosis among patients undergoing MDR-TB treatment at two community hospitals in Ethiopia.MethodsA case-control study design was conducted from February 1, 2016, to April 29, 2016. TB-positive patients with MDR-TB and non-MDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 18 publications
24
60
0
1
Order By: Relevance
“…MDR-TB was significantly associated with residence area; living in a rural area increased the occurrence of MDR-TB compared with living in an urban area. This is similar to the studies conducted in east Shoa, Oromia region and Amhara regional state, Ethiopia [23,24,25]. This could be due to the huge proportion of people living rural area, difference in access to TB services, socio-economy and the level of knowledge about adherence to first-line anti TB treatment, as rural communities have poor adherence to treatment that likely leads to the MDR-TB [23].In contrast, a study conducted in southwestern Ethiopia showed that rural residence was not associated with the development of MDR TB [22].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…MDR-TB was significantly associated with residence area; living in a rural area increased the occurrence of MDR-TB compared with living in an urban area. This is similar to the studies conducted in east Shoa, Oromia region and Amhara regional state, Ethiopia [23,24,25]. This could be due to the huge proportion of people living rural area, difference in access to TB services, socio-economy and the level of knowledge about adherence to first-line anti TB treatment, as rural communities have poor adherence to treatment that likely leads to the MDR-TB [23].In contrast, a study conducted in southwestern Ethiopia showed that rural residence was not associated with the development of MDR TB [22].…”
Section: Discussionsupporting
confidence: 90%
“…This might be due to drug mal-absorption in HIV infected patients since the patient is taking both ART medication and anti TB medications, especially ethambutol and rifampicin can lead to drug-resistance and treatment failure [26]. In contrast, HIV was not associated with the occurrence of MDR-TB in a study conducted in southwestern and, east Shoa, Ethiopia [22,23]. This discrepancy might be due to the sample size difference.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations